Analyzing the role of public expenditures in human development: panel data analysis of EU-28 countries - Linhartová, Veronika (My University, 2021)
A number of studies have already shown that public expenditure in human capital development is the investment with the highest return in the form of higher economic performance. National governments are fully aware of this, and they are seeking to stimulate human capital and encourage its development. The aim of this paper was to verify whether public expenditure in areas producing goods and services developing human capital really contributes to its development in EU-28 member countries. The COFOG government expenditure and the Human development index are the variables that were chosen for this analysis. The panel data analysis for the sample of the 28 EU countries in the period 1995-2018 was applied to test the hypotheses. Hausman test recommended a model with fixed effects as the most suitable method for performing the analysis. The panel estimation of the relationship between public spending and human development proved that public spending has both positive and negative impact on human development. The model with fixed effects showed that public expenditure on recreation, culture, and religion has the highest positive effect on human development, followed by health, social protection, housing and community amenities in descending order. A negative statistically significant impact on human capital development was demonstrated for public spending on environmental protection. The analysis of panel data showed that some areas of public expenditure cultivate human capital, while some areas of public expenditure may have the opposite effect.
Analýza role veřejných výdajů v lidském rozvoji: panelová analýza dat zemí EU-28
Keywords: public expenditures; Human Development Index; panel data; EU member countries; fixed effects model; veřejné výdaje; Index lidského rozvoje; panelová data; členské země EU; model s fixními efekty